On-farm salmonella testing: perspectives of pork producers - Mark, D.R.; Boland, Michael A.; Fox, John A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Pork producers in Kansas were surveyed to determine their attitudes regarding onfarm Salmonella testing and to provide estimates ofthe costs ofcollecting hide, fecal, or blood samples from live pigs. Veterinarians and Cooperative Extension Service personnel were cited most frequently as the most preferred groups for monitoring and verification. Results ofthe survey indicate that pork producers may be willing to conduct on-farm Salmonella testing, if they can recover the costs of sample collection. The sampling costs ranged from $1.76 to $4.72 per pig, depending on the method of sample collection.
Keywords: Swine; On-farm testing; Preharvest HACCP; Salmonella